Strain and Opportunity Structures - Hoffmann, John P. (Journal of quantitative criminology, 2004)
Traditional strain theory received substantial empirical attention for a prolonged period of time, but it currently occupies a marginal position in criminology. Efforts to revitalize and elaborate it have occurred under the rubric of Agnew's general strain theory. These theories share a focus on how contextual factors, in particular what are commonly referred to as opportunity structures, affect the relationship between stresses and strains and delinquency. Using national-level data, this study considers empirically the impact of several illegitimate opportunity structures conceptualized at the school-level on the association between strain, stressful life events, delinquency, and self-concept. The results indicate that both stress and strain affect changes in delinquency and self-concept over time. Yet there is little evidence that these relationships are conditioned by access to illegitimate opportunity. These results suggest that strain and stress affect delinquency uniformly across a variety of illegitimate opportunity structures.